(untitled) (Fiep Bulletin - online, 2015)
This article is about the history of children and adolescents in situation of risk that arrive in Canudos, a poor zone in the city of Novo Hamburgo in the state of Rio Grande do Sul. The context in which these children and adolescent are shown is that of the project “Crianças de Canudos” (Children of Canudos) from Feevale, a small local university. A school in the area was chosen as case study. It is discussed here the issue of university extension, and the colaboration between extension programs and physical education. The research problem is summarized in the question ’ What is the importance of Feevale’s Project Children of Canudos in the life of children and adolescents who are in a situation of risk?’ The methodology used for the investigation was the descriptive interpretative qualitative one with a case study. The instruments for data collection were interview, observation, documents, the researcher’s journal, and questionnaire. During the analysis and interpretation phase , 85 meaning units were obtained; these units resulted in two big categories, and four subcategories. At the school focused here, there were 29 children/adolescents, who participate in the projetct, in risky situation. The conclusion is that even those children/adolescents living with their families are in situations of risk.Factors such as family violence, prostitution, abuse/ill care, drugs, learning difficulties were found in the 24 participants who answered the questionnaire. For these children and adolescents, the importance of the Project is that in taking part in it, they can ’forget the bad times’ for a while, contemplate the possibility of a better life with people who show affection and interest for them. A highly positive aspect to be pointed out is that in spite of the context of risk in which they live, these children and adolescents still have dreams and expectations of finding a job (not necessarily a profession), remaining at school, having a better family, among others.